Effect of Corporate Governance Mechanism and Operating Cash Flow on Financial Distress - Etti Ernita Sembiring (Jurnal Bisnis dan Akuntansi, 2022)
This study aims to examine the effect of corporate governance mechanisms and operating cash flows on financial distress. The variable of corporate governance mechanism is measured through managerial ownership, institutional ownership, and audit committee. Managerial ownership can reduce conflicts of interest between principals and agents, while institutional ownership and audit committees are related to increasing supervision over company management. So, a good corporate governance mechanism can avoid financial distress. The adequacy of operating cash flow also greatly affects the efficiency and effectiveness of the company's operational activities. If the company has a negative operating cash flow, it will greatly hamper the company's operational activities. Companies can experience financial distress. This study uses data from manufacturing companies that have negative EBIT values ​​for two years from three years of observation in 2017-2019 as the research sample. This study uses the SEM-PLS analysis tool to answer the proposed hypothesis. The results showed that managerial ownership, institutional ownership, and audit committee had no significant effect on financial distress while operating cash flow negatively significantly effect of financial distress. The greater the operating cash flow value, the smaller the possibility of the company experiencing financial distress. Conversely, the smaller the operating cash flow value, the greater possibility of the company experiencing financial distress.